Swansea and Nantgarw Porcelains : A Scientific Reappraisal - Edwards, Howell G.M (Springer International Publishing : Imprint: Springer, 2017)
This book describes a holistic study of the porcelain manufactured at Nantgarw and Swansea in the first quarter of the 19th Century, using both scientific analytical data and historical provenancing. This porcelain is acclaimed as some of the finest and most translucent porcelain ever produced. These two porcelain factories are linked through the artistic and creative activities of the enigmatic William Billingsley and had a strictly limited production over only three or four years during the period 1812-1820. The earliest chemical analysis of these porcelains were undertaken almost 100 years ago and are compared with the results of more recent analyses The chemical composition of these porcelains, their artistic decoration and the struggle to maintain quality production is reviewed. Scientific explanations are proposed for the characteristic Swansea duck-egg porcelain translucency and for the Nantgarw iridescence. The book is well illustrated throughout and affords a good basis for the further in-depth study of Swansea and Nantgarw porcelains.
Keywords: Materials science.; Fine arts.; Cultural heritage.; Analytical chemistry.; Chemistry -- History.; Spectroscopy.; Microscopy.; Ceramics.; Glass.; Composites (Materials).; Composite materials.; elektronické knihy; electronic books